The Olympic Games as a career change-event: Israeli athletes' and coaches' perceptions of London 2012. (May 2016) - Samuel, Roy David; Tenenbaum, Gershon; Gil Bar-Mecher, Hila
Abstract: Objectives: This study used the Scheme of Change for Sport Psychology Practice (SCSPP; Samuel & Tenenbaum, 2011a) to examine athletes' and coaches' personal characteristics, perceptions of, coping with, and perceived outcome of the London 2012 Olympic Games (OGs). We also contrasted several sub-groups (e.g., Olympic and Paralympic athletes) in certain variables, and examined the decision-making and support systems involved in the OGs change process. Design and methods: A cross-sectional and retrospective design was used. Israeli Olympic and Paralympic athletes and coaches (N = 61) completed measures of change-event experiences (Samuel & Tenenbaum, 2011b) and athletic/coaching identity (AI/CI; Brewer & Cornelius, 2001) two years after the London 2012 OGs. Results: Olympic athletes trained more, and had higher motivation and AI than Paralympic athletes. The OGs were perceived as a significant and positive change-event in the participants' careers. AI/CI was associated with the perceived significance of the OGs. At the time of Olympic qualification, the participants tended either to ignore this change-event or cope with it independently. Most participants reported making a decision to change related to adjustment and coping. Professional support was mainly available prior to and during the OGs. During this experience the participants did not consider using sport psychology services, but retrospectively, valued the usefulness of this support. Athletes' motivation after the OGs was predicted from their satisfaction of coping, and their perceived outcome of this change-event was predicted from their satisfaction of competition results. Conclusions: Psychological support must be provided as part of the Olympic cycle, especially in promoting a decision to change. Maintaining realistic expectations may be critical for facilitating a positive perception of this change-event. Highlights: The OGs experience was perceived as a positive career change-event. Perceived significance was positively associated with athletic/coaching identity. The participants tended to make a decision to change related to adjustment and coping. Satisfaction of coping process predicted athletes' sport motivation after the OGs experience. Satisfaction of OGs competition results predicted the outcome of the change process.